Review article on Analytical Techniques of Lamivudine Determination in Different Matrices - E. Saraya Roshdy; Elhenawee Magda; Saleh Hanaa; M. Sebaiy Mahmoud (Journal of Advanced Pharmaceutical Science And Technology, 2021)
In this literature review, we will introduce most of up-to-date reported methods that have been developed for determination of lamivudine in its pure form, combined form with other drugs, combined form with degradation products, and in biological samples.
Keywords: DNA